Pengembangan E-Book Interaktif berbasis Aplikasi Calibre untuk Meningkatkan Keterampilan Menulis Siswi Kelas X MA Unggulan KH. Abd. Wahab Hasbullah Tambakberas Jombang - Maisaroh, Maulida Eva; Aisa, Aufia; Rahmawati, Rina Dian (Lembaga Yasin AlSys, 2025)
Writing instruction at MA Unggulan K.H. ABD Wahab Hasbullah, Tambakberas Jombang, remains heavily reliant on conventional textbooks, which tend to be less engaging and insufficient in motivating students effectively. This study aims to (1) develop an interactive e-book using the Calibre application to enhance writing skills, (2) test its effectiveness, and (3) assess its feasibility. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The study involved 39 tenth-grade students from class X-4, with data collected through material expert validation, media expert validation, pre-test and post-test, and student response questionnaires. Validation results indicated that the interactive e-book received an excellent feasibility rating: 100% from the material expert, 92.5% from the media expert, and 97% from student responses. The effectiveness test, measured using the N-Gain method, yielded an average score of 0.58 (moderate category), indicating an improvement in writing skills following the use of the e-book. It is concluded that the interactive e-book developed using the Calibre application is highly feasible and effective for teaching writing skills. The findings suggest that Calibre-based learning media offer an innovative, interactive, and flexible alternative that can enhance learning motivation, foster active student engagement, and support independent learning across various subjects.